Manajemen Ilmu Pendidikan dalam Perspektif Riset Global: Dinamika Digitalisasi, Etika, dan Tata Kelola di Era Transformatif: Educational Science Management in a Global Research Perspective: The Dynamics of Digitalization, Ethics, and Governance in a Transformative Era - Sudiansyah, Sudiansyah; Rostina, Rostina; Peterianus, Septian; Simin, Simin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The transformation of education in the digital era has created new challenges and opportunities in governance, leadership ethics, and technological integration. This study aims to examine educational management from a global research perspective by highlighting the dynamics of digitalization, ethical principles, and governance policies. A qualitative multidisciplinary approach was employed using a systematic literature review (SLR). Data were sourced from 40 high-reputation scientific publications, including Scopus, Web of Science (WoS), SINTA, and DOAJ indexed journals. The data were analyzed through thematic analysis and narrative synthesis. The findings reveal five main points: (1) global trends indicate a shift towards reflective and collaborative leadership; (2) digitalization is driving the adoption of AI-based learning systems and big data; (3) ethical principles are a key determinant of the credibility of educational governance; (4) educational policies require cross-cultural contextual adaptation; and (5) a gap persists between the integration of theory and practice. In conclusion, modern educational management needs to be developed through a multidisciplinary approach that combines digital innovation, ethical values, and sensitivity to the global context.